Is home-based monitoring of ovulation to time frozen embryo transfer a cost-effective alternative for hospital-based monitoring of ovulation? Study protocol of the multicentre, non-inferiority Antarctica-2 randomised controlled trial. Issue 4 (1st October 2021) - Zaat, T R; de Bruin, J P; Goddijn, M; van Baal, M; Benneheij, E B; Brandes, E M; Broekmans, F; Cantineau, A E P; Cohlen, B; van Disseldorp, J; Gielen, S C J P; Groenewoud, E R; et al.
Abstract: STUDY QUESTION: The objective of this trial is to compare the effectiveness and costs of true natural cycle (true NC-) frozen embryo transfer (FET) using urinary LH tests to modified NC-FET using repeated ultrasound monitoring and ovulation trigger to time FET in the NC. Secondary outcomes are the cancellation rates of FET (ovulation before hCG or no dominant follicle, no ovulation by LH urine test, poor embryo survival), pregnancy outcomes (miscarriage rate, clinical pregnancy rates, multiple ongoing pregnancy rates, live birth rates, costs) and neonatal outcomes (including gestational age, birthweight and sex, congenital abnormalities or diseases of babies born). WHAT IS KNOWN ALREADY: FET is at the heart of modern IVF. To allow implantation of the thawed embryo, the endometrium must be prepared either by exogenous oestrogen and progesterone supplementation (artificial cycle (AC)-FET) or by using the NC to produce endogenous oestradiol before and progesterone after ovulation to time the transfer of the thawed embryo (NC-FET). During an NC-FET, women visit the hospital repeatedly and receive an ovulation trigger to time FET (i.e. modified (m)NC-FET or hospital-based monitoring). From the woman's point of view, a more natural approach using home-based monitoring of the ovulation with LH urine tests to allow a natural ovulation to time FET may be desired (true NC-FET or home-based monitoring). STUDY DESIGN, SIZE, DURATION: This is a multicentre, non-inferiority prospective randomised controlled trial design. Consenting women will undergo one FET cycle using either true NC-FET or mNC-FET based on randomisation. PARTICIPANTS/MATERIALS, SETTING, METHODS: Based on our sample size calculation, the study group will consist of 1464 women between 18 and 45 years old who are scheduled for FET. Women with anovulatory cycles, women who need ovulation induction and women with a contra indication for pregnancy will be excluded. The primary outcome is ongoing pregnancy. Secondary outcomes are cancellation rates of FET, pregnancy outcomes (including miscarriage rate, clinical pregnancy, multiple pregnancy rate and live birth rate). Costs will be estimated by counting resource use and calculating unit prices. STUDY FUNDING/COMPETING INTEREST(S): The study received a grant from the Dutch Organisation for Health Research and Development (ZonMw 843002807; www.zonmw.nl ). ZonMw has no role in the design of the study, collection, analysis, and interpretation of data or writing of the manuscript. F.B. reports personal fees from member of the external advisory board for Merck Serono, grants from Research support grant Merck Serono, outside the submitted work. A.E.P.C. reports and Unrestricted grant of Ferring B.V. to the Center for Reproductive medicine, no personal fee. Author up-to-date on Hyperthecosis. Congress meetings 2019 with Ferring B.V. and Theramex B.V. M.G. reports Department research and educational grants from Guerbet, Merck and Ferring (location VUMC) outside the submitted work. E.R.G. reports personal fees from Titus Health Care, outside the submitted work. C.B.L. reports grants from Ferring, grants from Merck, from Guerbet, outside the submitted work. The other authors have none to declare. TRIAL REGISTRATION NUMBER: Dutch Trial Register (Trial NL6414 (NTR6590), https://www.trialregister.nl/ ). TRIAL REGISTRATION DATE: 23 July 2017 DATE OF FIRST PATIENT'S ENROLMENT: 10 April 2018